Methodology of teaching writing scientific articles in English - Xolmatova, Maxbubaxon (The Lingua Spectrum, 2025)
This article analyzes the methodology and effective teaching methods for writing scientific articles in English. The process of writing a scientific article is examined based on academic writing standards, stylistic features, and a clear logical structure. The study discusses the main methods of scientific writing, including inductive and deductive approaches, genetic and reproductive methods, collaborative writing, modeling, peer review, and reflective writing techniques. Additionally, the significance of interactive approaches and the use of modern technologies in enhancing the effectiveness of scientific writing is highlighted. The research findings confirm the effectiveness of integrative and communicative approaches in developing scientific writing skills in English.This article is devoted to the topic of Methodology of Teaching Writing Scientific Articles in English and is aimed at studying the main strategies and methods for developing the skills of writing scientific articles, as well as their types. The features of using the IMRAD method in writing scientific articles are studied, as well as possible shortcomings in the process of teaching writing articles and ways to eliminate them.